Digital Transformation Adoption Among SMEs in Developing Economies: Evidence from Nawalparasi District, Nepal - Gupta, Kanhaiya (Nexus: Journal of Interdisciplinary Engineering, Technology and Management, 2026)
Small and medium-sized enterprises play a vital role in economic development in developing countries, yet structural, institutional, and organizational challenges often constrain their progress toward digital transformation. This study examines the factors influencing the adoption of digital transformation among SMEs in Nawalparasi, focusing on four dimensions: business environment, innovation, digital capabilities, and digital tools. The study is grounded in the Technology–Organization– Environment framework, the Technology Acceptance Model, and Innovation Diffusion Theory. Using a quantitative cross-sectional survey design, data were collected from 237 SME owners, managers, and employees. Yamane’s sampling formula was applied to determine the sample size from a population of 27,300 registered SMEs, and the data were analyzed using descriptive statistics, Pearson correlation, and multiple linear regression with IBM SPSS Statistics 27.The findings indicate that digital tools and innovation are the two significant predictors of digital transformation adoption among SMEs. Digital tools emerged as the strongest predictor, demonstrating that firms with greater access to and use of digital technologies are more likely to adopt digital transformation practices. Innovation also showed a positive and significant influence, suggesting that organizations with a stronger culture of experimentation and openness to change are more inclined to adopt digital technologies. In contrast, the business environment and digital capabilities did not independently predict firm-level adoption. Although digital capabilities were statistically not significant in the regression model, they had the lowest mean, highlighting major deficiencies in digital strategy, workforce training, and organizational readiness among SMEs in Nawalparasi. A notable finding of the study is the paradox between organizational preparedness and perceived outcomes. Despite weaknesses in strategic capability and training, respondents expressed strong satisfaction with the outcomes of digital transformation. This suggests that SMEs are experiencing the immediate benefits of digitalization while still lacking the deeper organizational infrastructure required for sustainable transformation.